A PIT‐tag–based method for measuring individual bait uptake in small mammals. Issue 2 (17th June 2021) - Beatham, Sarah E.; Goodwin, Dominic; Coats, Julia; Stephens, Philip A.; Massei, Giovanna
Abstract: Rodents and other small mammals cause an increasing number of negative economic and environmental impacts worldwide. In the UK, the non‐native grey squirrel has a significant impact on the forestry industry and has caused the decline of the native red squirrel. Baits are used to deliver biocides and contraceptives to reduce overabundant wildlife populations and as vehicles for vaccines to control disease outbreaks. Bait‐delivered contraceptives are also being developed to manage grey squirrel populations in the UK. The effectiveness of bait‐delivered drugs on wildlife populations depends on the amount of bait consumed by individuals over time; therefore, it is important to understand individual level bait uptake in order to optimize delivery methods. Passive integrated transponder (PIT) tags are increasingly used to mark and monitor animal behaviour as they are cost‐effective, have minimal negative welfare impacts and have a lower tag loss rate than external tags, particularly in small animals. The aim of this study was to design and test a novel bait hopper equipped with a PIT‐tag reader and bait‐weighing device, to record bait uptake by individual grey squirrels for optimizing the delivery of a contraceptive bait. The hopper was designed to overcome some of the limitations of traditional PIT‐tag systems, by improving battery life and the quality and quantity of data collected in the field. In captive trials, the hopper proved to be highly effective at recording feeding visits by squirrels, as 95% of the visits could be attributed to a PIT‐tag record. The hoppers measured the amount of bait removed per feeding visit to an accuracy of 0.1 g, with 97% of the bait taken from six hoppers attributed to a PIT‐tag ID. In a field trial, the hoppers were effective at recording the feeding visits by grey squirrels in two woods, with 47 of the 51 PIT‐tagged grey squirrels entering the hoppers. The adaptability of the hopper design means that it has wider applications for wildlife management; in particular, efficacy studies for bait‐delivered substances in the context of wildlife disease control and/or population reduction. Abstract : The novel design of hopper with integrated PIT‐tag reader and bait weighing capability proved highly effective at measuring patterns and quantities of bait uptake by individual grey squirrels. The unique modifications to the hopper design in this study resulted in improved data collection and battery life in the field when compared to other similar devices. The adaptability of the hopper design means that it has wider applications for wildlife management; in particular, efficacy studies for bait‐delivered drugs in the context of wildlife disease control and/or population reduction.